2021
DOI: 10.1109/access.2021.3062493
|View full text |Cite
|
Sign up to set email alerts
|

DeepKneeExplainer: Explainable Knee Osteoarthritis Diagnosis From Radiographs and Magnetic Resonance Imaging

Abstract: Osteoarthritis (OA) is a degenerative joint disease, which significantly affects middleaged and elderly people. Although primarily identified via hyaline cartilage change based on medical images, technical bottlenecks like noise, artifacts, and modality impose an enormous challenge on high-precision, objective, and efficient early quantification of OA. Owing to recent advancements, approaches based on neural networks (DNNs) have shown outstanding success in this application domain. However, due to nested non-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Table 1 shows that previous studies [ [70] , [71] , [72] , [73] , [74] , 82 ] have achieved the minimum accuracy of 91% for multicenter osteoarthritis studies using chest x-ray images, and the maximum accuracy of 98.3% for COVID-RENet and COV-VGGNet models. Some other authors [ 75 , 76 ] reported a maximum accuracy of 94% for CT images using the DRENet model and lower accuracy of 76.47% for the JRIP model.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Table 1 shows that previous studies [ [70] , [71] , [72] , [73] , [74] , 82 ] have achieved the minimum accuracy of 91% for multicenter osteoarthritis studies using chest x-ray images, and the maximum accuracy of 98.3% for COVID-RENet and COV-VGGNet models. Some other authors [ 75 , 76 ] reported a maximum accuracy of 94% for CT images using the DRENet model and lower accuracy of 76.47% for the JRIP model.…”
Section: Resultsmentioning
confidence: 97%
“… SqueezeNet Chest X ray Image 98 [ 71 ] ResNet18 98 [ 71 ] ResNet50 98 [ 71 ] DenseNet-121 98 [ 71 ] 3. Multicenter Osteoarthritis Study Chest X-ray Image 91 [ 72 ] 4. SDD300 model Chest X-ray Image 94.92 [ 73 ] 5.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the KL scoring system has been widely used in clinics, some scholars still question the rationality of KL grading [26,27]. The method proposed by Karim et al, based on MRI (magnetic resonance imaging) and X-ray, can get 91.45% accuracy [28]. We will try to use the CT or MRI dataset to help improve the model accuracy during the training to get more depth information.…”
Section: Discussionmentioning
confidence: 99%
“…The development of deep learning (DL) has made it possible to establish accurate and rapid diagnostic methods (8). DL can allow the learning of features directly from the data, and it has recently revolutionized the field of medical image analysis by surpassing the conventional computer vision techniques that require the manual engineering of data representation methods (9). DL can undertake tasks such as image alignment, image recognition, image detection, image segmentation, and image classification and prediction, among others (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…DL can undertake tasks such as image alignment, image recognition, image detection, image segmentation, and image classification and prediction, among others (10)(11)(12)(13)(14)(15)(16). These DL models include the well-known U-Net network and Residual Net (ResNet) network (9,17). In terms of medical image processing, the DL model can automatically extract the features of X-ray images through the learning of neural networks and classify the images to assist clinicians in diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%